The complete mitochondrial genome of the Draco maculatus (Squamata: Agamidae). Issue 1 (2nd January 2019) - Qiu, Qing-Bo; Zhu, Guan-Yan; Yu, Xiu-Li; Du, Yu
Abstract: We report the complete mitogenome of Draco maculatus, which is 16, 708 bp in size and includes 13 protein-coding genes (PCGs), two rRNA genes, 22 tRNA genes, and a control region. PCGs, with 13 genes, is 11, 280 bp in length. All PCGs use ATN as the start codon; COI, ATP8, ND4L, ND5, and Cytb use the typical stop codon TAA; but ATP6, COIII, and ND3 stop with a single T. Phylogeny reconstructed using the Bayesian inference (BI) method with 13 PCGs indicates that D . maculatus is located at the root of Draconinae.